Adverse childhood experiences, mothers and homelessness: a narrative review and recommendations - Kohler, Ashley; Pylypchuk, Nicole; Reisdorfer, Emilene (My University, 2024)
Homelessness is a complex and pervasive worldwide social crisis that profoundly affects a diverse range of individuals and communities. Adverse childhood events (ACEs) are traumatic events that can lead to significant negative effects during adulthood, including homelessness. In women who are mothers, the pathways to loss of housing include, but are not limited to: a history of ACEs, weak social networks, sexual violence, and intimate partner violence. This narrative review of the literature aimed at examining the evidence of adverse childhood experiences and homelessness in adult women who are mothers and to providing recommendations for practice. Across the eight articles included and analyzed, six common themes emerged: family fragmentation, out-of-family placement, abuse, learned substance abuse, a lack of formal and informal education, and normalization and internalization of ACEs. The results showed that children who experience ACEs and become mothers in adulthood might have increased chances of becoming homeless and repeating an intergenerational cycle of trauma onto their children.
Keywords: homelessness; motherhood; women; adverse childhood experiences